"Vocation; Its Styles and Indications in Divan "Alshoaa" for poet " Walid-Al-Adhami - Al-Kubaisi, Khalil Ibrahim Mudhebi (Arab Journal for Sciences and Research Publishing, 2019)
The research dealt with the phenomenon of the vocation as a manner that has grammatical and rhetorical significance or connotation at Arab scholars (scientists), and how poets use the energies of style to express what they want to raise in the hearts of the recipients: readers or listeners. Such as the supplication phenomenon is striking in the stylistic poet, and this was obvious at the Iraqi poet" Walid Al-Adhami ' in his divan "Alshoaa' and the vocation came varied in:-The nature of vocative, as appeal or supplication of the Prophet, peace and blessings of God be upon him, and call for the example, and the mobilization of the nation, and a call to highlight the position of the poet from the enemies of the nation and their agents, and to celebrate brave national figures.-The ability of the poet in the dramatic construction of some of his poems has become clear, although his language is direct and preaching.The poet vary between the different vocative manners, and tools, although "Ya" is the most used tool.The rhetorical images were few, and the expressive suggestions were rare for the poet's desire for public enthusiasm.
Keywords: The call; grammar; rhetoric; poetry